Kajian Penandaarasan Bidang Tumpuan Utama Dalam Pembangunan Strategi Sebuah Zoo Di Malaysia (Benchmarking Study on Key Focus Area in Strategy Development of a Zoo in Malaysia) - Jimoh, Abdulrazaq Taiye; Zahari, Fadhilah; Osman, Nor Hasni; Ahmad, Azhar; Ramli, Mat Naim; Abidin, Rahimi (UUM Press, 2018)
Strategic management is very important in ensuring the continuity and sustainability of an organization, especially business organizations. Similarly, to ensure the survival of an organization such as a zoo which is largely of its financial resources depends on the sustainability of business operations. This article discusses about a study conducted to identify the key of focus areas in developing the best strategy for Zoo Negara, one of the zoo in Malaysia. A Benchmarking study was conducted to identify the key of focus areas and practices adopted by leading zoos from States of America, Australia, and Canada. A field study was also conducted at three zoos in Thailand to make a comparative and well-known focus area. The findings show that there are six main focus areas that need to be emphasized in ensuring Zoo Negaras performance. This study has practical implications for zoo management to develop appropriate strategies.